Suggestive linkage and association of preserved cognition to chromosome 18 in genetically at‐risk Amish. (December 2021) - Dorfsman, Daniel A.; Prough, Michael B.; Caywood, Laura J.; Close, Jason E.; Herington, Sharlene D.; Slifer, Susan H.; Adams, Larry D.; Laux, Renee A.; Song, Yeunjoo E.; Lynn, Audrey; Sewell, Jane L.; Miller, Sherri D.; et al.
Abstract: Background: Previous studies have identified genetic risk factors for Alzheimer Disease (AD). In the Amish community, many individuals maintain normal cognitive function at older ages, despite having relatively high genetic risk of AD. These individuals may carry protective alleles that buffer the genetic risk. To find such loci, we utilized the Amish family structures to apply a modified genetic linkage analytical tool that considered genetic risk of AD. Method: Cognitive status in adult Amish subjects (n=1, 855) was assigned using the modified mini‐mental status exam (3MS). Individuals aged ≥ 75 with 3MS ≥ 87 were classified as CN. Those with 3MS < 87 were classified impaired (CI), regardless of age. Genome‐wide genotypes were used to impute ∼7 million variants using the HRC imputation reference panel. For genome‐wide linkage analysis, we selected 2, 167 SNPs and analyzed 110 sibships with ≥ 2 CN members. Adjusting for known genetic risk, we applied ordered subsets analysis (OSA) to rank families by mean Genetic Risk Score (GRS) of CN members. GRS was derived from 27 genome‐wide AD loci (Kunkle et al, 2019). Regions with significant increases in linkage (LOD*) were assessed by mixed model genetic association testing. Result: Ranking sibships by high‐to‐low mean GRS, significant increases in the LOD* after OSA were observed at ∼40 Mb on chromosome (Chr) 19 (peak LOD*=2.176, p=0.009) and ∼49 Mb on chr 18 (peak LOD*=2.23, p=0.03). While linkage to chr 19 may result from known AD loci, the observed linkage to chr 18 does not overlap known risk loci. Mixed model association testing within a 5 Mb region of the peak linkage to chr 18 was performed in 1, 036 SNPs with minor allele frequency ≥ 0.01. Individuals with a GRS ≥ 3.65, corresponding to the GRS in the 17 families with the strongest LOD* increase, were considered (n=236). The strongest association occurred at rs12969463 (p=0.002, OR = 2). Conclusion: This study detected increased evidence of linkage and association for protective AD loci on chr 18, considering CN individuals with the highest risk from known AD loci. One or more protective alleles that buffer this increased risk may be located in this region.